NA

Cho a+b+c=0 CMR:\(\left(a^2+b^2+c^2\right)^2=2\left(a^4+b^4+c^4\right)\)

HH
13 tháng 10 2018 lúc 21:17

Từ a+b+c=0 có b+c =-a 
Suy ra (b+c)^2 = (-a)^2 hay b^2 + c^2 +2bc = a^2 
hay b^2 + c^2 -a^2 = -2bc 
Suy ra (b^2 + c^2 - a^2)^2 = (-2bc)^2 
<=> b^4 + c^4 + a^4 +2b^2.c^2 - 2a^2.b^2 - 2a^2.c^2 = 4b^2.c^2 
<=> a^4 + b^4 + c^4 = 2a^2.b^2 + 2b^2.c^2 + 2c^2.a^2 
<=> 2(a^4 + b^4 + c^4) =a^4 + b^4 + c^4 + 2a^2.b^2 + 2b^2.c^2 + 2c^2.a^2 
<=> 2(a^4 + b^4 + c^4 ) =(a^2 + b^2 + c^2)               ( Đpcm)

Bình luận (0)
KS
13 tháng 10 2018 lúc 21:31

Ta có: \(a+b+c=0\)

\(\Rightarrow\left(a+b+c\right)^2=0\)

\(a^2+b^2+c^2+2ab+2bc+2ca=0\)

\(\Rightarrow a^2+b^2+c^2=-2.\left(ab+bc+ca\right)\)

\(\Rightarrow\left(a^2+b^2+c^2\right)^2=\left[-2.\left(ab+bc+ca\right)\right]^2\)

\(a^4+b^4+c^4+2a^2b^2+2b^2c^2+2c^2a^2=4a^2b^2+4b^2c^2+4c^2a^2+4abc\left(a+b+c\right)\)

\(a^4+b^4+c^4=2a^2b^2+2b^2c^2+2c^2a^2\)

\(\left(a^2+b^2+c^2\right)^2=a^4+b^4+c^4+2a^2b^2+2b^2c^2+2c^2a^2\)

\(\Rightarrow\left(a^2+b^2+c^2\right)^2=a^4+b^4+c^4+a^4+b^4+c^4\)

\(\Rightarrow\left(a^2+b^2+c^2\right)^2=2.\left(a^4+b^4+c^4\right)\)

                                                   đpcm

Tham khảo nhé~

Bình luận (0)

Các câu hỏi tương tự
VK
Xem chi tiết
KK
Xem chi tiết
NA
Xem chi tiết
NA
Xem chi tiết
CT
Xem chi tiết
CD
Xem chi tiết
NL
Xem chi tiết
NA
Xem chi tiết
TH
Xem chi tiết